Diversity, conflict, and leadership - Rahim, M. Afzalur (New Brunswick, N.J. : Transaction Publishers, 2011)
Current Topics in Management, of which this book is Vol. 15, is a peer-reviewed scholarly journal which presents basic research in the theory and practice of management and administration. In these twelve essays, a multinational group of experts consider issues of organizational conflict from the small-business level up to that of international commerce and politics.
Preface / M. Afzalur Rahim -- Managing diverse situations in organizations / M. Afzalur Rahim-- Part I : managing conflict and justice -- The moderating role of social attitudes in the relationship between diversity and conflict / Nailah Ayub and Karen A. Jehn -- Moderating effects of geographic dispersal and team tenure on the task-affective conflict relationship / Patricia J. Holahan, Ann C. Mooney, and Laura Finnerty Paul -- Fairness and consumer behavior : a WWJD (what would justice do?) analysis / Kelly Schwind Wilson, Donald E. Conlon, and Joel Koopman -- Part II : Leadership, social capital and personality -- Obama vs. Clinton : a study exploring the impact of leadership language / Diana Hargrove, Phyllis A. Duncan, Mark T. Green, Charles Salter, and John M. Trayhan -- Social capital via leader-member exchanges : an avenue to human capital? / E. Edward Stark and Franis L. Jeffries -- Relationship between the big-five personality and the financial performance of fund managers / Selin Metin Camgoz, Mehmet Baha Karan, and Azize Ergenelli -- Part III : Issues in entrepreneurship and small business -- Modifying Phelan's model : a conceptual framework linking entrepreneurs to international new venture competitiveness / Florinel-Frank Cotae -- BSL Printing Company : a case study / Joseph P. Lakatos, Donald R. Soucy, and Stephen J. Bukowy -- Part IV : Ethics, learning, and change -- Ethics, rhetoric and the self as an expanding web of conversations / Can M. Alpaslan, Sandy E. Green, and Ian I. Mitroff -- Flexibility, learning and control : entry mode choice under uncertainty / Mujtaba Ashan and Martina Musteen -- The politics-administrative continuum in American state governments : administrative accountability as a positive-sum pattern / Cheryl Miller and Deil S. Wright -- About the contributors.
Includes bibliographical references.
Keywords: Communication in personnel management; Conflict management; Organizational behavior; Organizational change; Negotiation in business; Interpersonal confrontation; Culture conflict; Transformational leadership